PENGARUH MOTIVASI BELAJAR; SELF EFFICACY DAN LINGKUNGAN SEKOLAH TERHADAP PRESTASI BELAJAR SISWA - Djamil Mz, Masydzulhak; Sitanggang, Magdalena (Universitas Mercu Buana, 2017)
This study aims to analyze the influence of learning motivation; self efficacy; and school environment on learning achievement. Backed by the efforts of SMA Negeri 7 Kota Bekasi continue to strive to follow the development of the world of Education for the improvement of service quality; Human Resources and the quality of graduates. The object of research used is the students of SMA Negeri 7 Kota Bekasi from 3 classes representing all levels of education as many as 120 students. The sampling using Slovin formula so that the sample obtained 92 students SMA Negeri 7 Kota Bekasi. To analyze the research data used Partial Least Square (PLS) Version 3.0. The result of the research shows that (1) Learning Motivation has positive and significant effect on Student Learning Achievement of SMA Negeri 7 Kota Bekasi; (2) Self Effiacy has no significant effect on Student Learning Achievement of SMA Negeri 7 Kota Bekasi; (3) School Environment has positive and significant influence On Student Achievement of State Senior High School 7 Bekasi; and (4) Learning Motivation; Self Efficacy; and School Environment together significantly influence on Student Achievement of SMA Negeri 7 Kota Bekasi.